PENGEMBANGAN STRATEGI BISNIS UMKM PENGRAJIN TAS DI KUNCIRAN INDAH, KOTA TANGERANG - Nawawi, M. Tony; Darryl; Said Ashadi Cahyadi (Jurnal Serina Abdimas, 2025)
The development of SME business strategies is very important for an entrepreneur to maintain the continuity of his business, through this marketing strategy can provide operational solutions for his business in the future. A business is said to be successful if the business has a measurable business marketing strategy. This Community Service Activity aims to help Home Businesses (MSMEs) business marketing strategies in running their business. The Community Service Partners are Home Businesses engaged in the business of making waist bags which are processed into family businesses to earn household income. In its implementation, partner businesses require the development of business strategies, especially in maintaining the sustainability of their businesses, because in order to compete with other parties. This is due to the lack of partner knowledge about marketing business strategies. For this reason, Community Service activities aim to help partners increase their knowledge in terms of developing optimal business strategies. The method offered in this activity is offline socialization. The material to be presented includes: introduction to strategy, benefits of business plans, business plan formats and others. Through this activity, it is hoped that problems that arise in partner businesses will be resolved quickly, partners can understand the importance of developing business strategies in running their businesses. ABSTRAK Pengembangan strategi bisnis UMKM sangat penting bagi seorang pengusaha untuk menjaga kelangsungan bisnisnya, melalui strategi marketing ini dapat memberikan solusi operasional bisnisnya di masa yang akan datang. Sebuah bisnis dibilang berhasil atau sukses bilamana, bisnisnya memiliki strategi marketing bisnis yang terukur. Kegiatan Pengabdian Kepada Masyarakat (PKM) kali ini bertujuan untuk membantu strategi marketing usaha rumahan (UMKM) dalam menjalankan bisnisnya. Adapun mitra Pengabdian Kepada Masyarakat (PKM) ini adalah usaha rumahan bergerak pada usaha pembuatan tas pinggang yang diolah menjadi bisnis keluarga untuk mendapatkan pendapatan rumah tangga. Dalam pelaksanaannya usaha mitra memerlukan pengembangan strategi bisnis terutama dalam menjaga keberlanjutan usahanya, karena untuk dapat bersaing dengan pihak lain. Hal ini dikarenakan minimnya pengetahuan mitra tentang strategi bisnis marketing. Untuk itu kegiatan Pengabdian Kepada Masyarakat bertujuan membantu mitra meningkatkan pengetahuan mitra dalam hal pengembangan strategi bisnis secara optimal. Metode yang ditawarkan pada kegiatan ini adalah sosialisasi secara luring. Materi yang akan disampaikan meliputi:pengenalan strategi, manfaat rencana bisnis, format rencana bisnis dan lainnya. Melalui kegiatan ini diharapkan, masalah yang muncul pada usaha mitra cepat diatasi, mitra dapat memahami pentingnya pengembangan strategi bisnis dalam menjalankan usahanya.